The Coinage and History of Achaiion in the Troad - Ellis-Evans, A (Presses Universitaires de Bordeaux, 2017)
Two issues of bronze coinage from the Troad with the monogram AX (late 4th/early 3 rd c. BC) have traditionally been attributed to Achilleion. However, excavations of Achilleion show that it was never more than a small fort. These coins should therefore be attributed to Achaiion, known to us from Strabo as the chief town of the nearby Tenedian peraia. In addition to the issues with the AX monogram, Achaiion also produced bronze coinage in the 2nd c. BC. It is argued that these two periods of minting probably represent periods of independence from Tenedos and thus prompt questions about the significance of the peraia to the Tenedian economy and the importance of bronze coinage in reconstructing the political history of the Hellenistic Troad.